Development of a guide on sodium content in food for hypertensive and normotensive people - Kayathtri, K.; Adikari, A.M.N.T. (Colombo : Sri Lanka Association for the Advancement of Science, 2021)
Hypertension (HTN) is a public health issue and the prevalence of hypertension is 26.1% in adults of age 18-69 in Sri Lanka. It is evident from several studies that dietary sodium reduction is an important measure for hypertension management and that food selection is a vital part when it comes to lowering sodium intake. In order to make lower sodium food choices, it is important that consumers are knowledgeable about sources of sodium, and its recommended levels of daily intake. The absence of any guide on sodium content of commonly consumed food in Sri Lanka prompted us to conduct this study to develop a guide on sodium content of commonly available food items for hypertensive and normotensive people in Sri Lanka. A preliminary survey was conducted with 30-60 years age range, 30 hypertensive patients to identify the dietary patterns, sodium rich foods that they consume, daily sodium intake and commonly available food using a pre-tested interviewer administered questionnaire, two 24-hour dietary-recalls, a food frequency questionnaire and direct observation of food available at markets and home-gardens. Sodium content of commonly available foods was determined using Sri Lankan, Indian and ASEAN food composition tables and food labels. Food was categorized into low (<120 mg/100 g), medium (120 600 mg/100 g) and high (>600 mg/100 g) sodium containing food according to the sodium content in 100 g of food. A booklet was developed by including functions of sodium, sodium rich food items, tables of food categorized according to sodium contained in per-portion of 61 commonly consumed food items and instructions on how to refer the booklet. The results of the preliminary survey showed that the mean intake of sodium (2298 ± 751 mg) was higher than the recommended daily intake (1500 mg/day) of hypertensive adults. The developed booklet consists of photographs of one portion of commonly consumed food with sodium content in “mg”. High, medium and low sodium containing food was indicated with the colours of red, yellow and green, respectively. This developed booklet may be a useful guide to select low sodium food for hypertensive patients to manage their condition and for healthy adults to prevent hypertensive condition.
Keywords: Guide-Booklet; Hypertension; Normotensive; Sodium Content